Modern Business Transformation Through Information Technology, Communication, And Digital Applications - S, Muh Rizal; Zainal, Nur Hikmah; Nasfat, Riska Amalia; Sinar, Syam; Wildani, Ainun (Universitas Negeri Makassar, 2025)
The transformation of modern businesses is driven by the advancements in information technology, communication, and digital applications, creating opportunities for innovation and efficiency. This study aims to analyze the role of digital technology in supporting operational efficiency, communication strategies, and market adaptation. The research method used is qualitative analysis with a literature review approach and case studies on several companies that have successfully adopted this technology. The analysis technique involves identifying patterns of technology adoption and its impact on productivity and customer satisfaction. The findings indicate that technology integration improves operational efficiency, expands customer reach, and accelerates data-driven decision-making.